KERJASAMA EKSPOR CRUDE PALM OIL (CPO) INDONESIA KE NEGARA VIETNAM PADA TAHUN 2012-2015 - Iga Rolesa Putri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This paper is a Bilateral Trade study that provides an analysis of the Cooperation of two countries in the fulfillment of needs and achieve their nasal interests. This research is focused on Indonesia Crude Palm Oil (CPO) Exports to Vietnam from 2012-2015. Crude Palm Oil is the result of processed pulp of palm fruits as vegetable oil which is needed as industrial material and household consumption. Where Indonesia as the world's largest producer of palm oil contributes 51% to the world's palm oil demand and engages in exports to various countries including VietnamThis paper uses a conceptual basis, with the concept of International Cooperation where here International cooperation is formed because of international life covering various fields such as ideology, politics, economy, social culture, environment and security defense. These problems have brought countries in the world to form an international cooperation. Supported by National Nation's analysis level and Liberalism Perspective. The concept leads to qualitative methods and field studies and is assisted by literature studies as a source of information.MoU on Cooperation between Indonesia and Vietnam is a form of Indonesia's national interest, where in bilateral cooperation between the two countries the final destination is profit. Therefore, the cooperation of CPO exports to be one of the many Indonesian exports to Vietnam to achieve the trade value set in the Plan of Action of both countries amounted to USD 10 billion.Keywords: Indonesia, Vietnam, Cooperation, Export, Crude Palm Oil